Analisis Beban Kerja guna Menentukan Tenaga Kerja Optimal Plant II di PT. Keramik Diamond Industries Gresik dengan Metode WLA - Wardana, Yoga Putra; Widiasih, Wiwin (SURYA TEKNIKA, 2026)
PT. Keramik Diamond Industries is a wall and floor tile manufacturing company required to meet production targets effectively and efficiently. In Plant II, the monthly production target of 400,000 m2 was not achieved from January to July 2025; therefore, an evaluation of labor requirements based on actual workload was needed. This study aims to determine the optimal number of workers in the Body Preparation, Press, Glazing, Kiln, and Grading processes using the Work Load Analysis (WLA) method. Data were collected through direct observation, stopwatch time study, production records, working-hour data, and workers’ pulse-rate measurements. The analysis stages included data uniformity and adequacy tests, cycle time calculation, normal time, standard time, standard output, WLA, and physical workload evaluation using Cardiovascular Load (CVL). The WLA results show that the optimal labor requirement is 36 operators compared with the actual condition of 20 operators, with the highest additional needs found in the Kiln and Body Preparation processes. The average CVL value of 63.92% indicates that work-system improvement is required. Adjusting the number of operators is expected to balance workload and support productivity improvement in Plant II.